Ultrasonic compatibilization of polyelectrolyte complex based on polysaccharides for biomedical applications - Belluzo, M. Soledad (2016)
In recent years, there has been an increasing interest in the design of biomaterials for cartilage tissue engineering. This type of materials must meet several requirements. In this study, we apply ultrasound to prepare a compatibilized blend of polyelectrolyte complexes (PEC) based on carboxymethyl cellulose (CMC) and chitosan (CHI), in order to improve stability and mechanical properties through the interpolymer macroradicals coupling produced by sonochemical reaction. We study the kinetic of the sonochemical degradation of each component in order to optimize the experimental conditions for PEC compatibilization. Scaffolds obtained applying this methodology and scaffolds without ultrasound processing were prepared and their morphology (by scanning electron microscopy), polyelectrolyte interactions (by FTIR), stability and mechanical properties were analyzed. The swelling kinetics was studied and interpreted based on the structural differences between the two kinds of scaffolds. In addition we evaluate the possible in vitro cytotoxicity of the scaffolds using macrophage cells in culture. Our results demonstrate that the ultrasound is a very efficient methodology to compatibilize PEC, exhibiting improved properties compared with the simple mixture of the two polysaccharides. The test with murine macrophage RAW 264.7 cells showed no evince of cytotoxicity, suggesting that PEC biomaterials obtained under ultrasound conditions could be useful in the cartilage tissue engineering field.